Prevalence of insomnia and its associated factors among rural elderly: a community based study - El-Gilany, Abdel-Hady; Saleh, Nadia; Mohamed, Heba; Elsayed, Eman (International Journal of Advanced Nursing Studies, 2017)
Background: Insomnia is a common problem among older adults and can lead to several complications affecting the quality of life of elderly people.Aim: To estimate the prevalence of insomnia and its associated factors among community-dwelling elderly.Study design: This is a cross-sectional descriptive study carried out on 1059 elderly living in three villages affiliated to Mansoura District, Egypt. Data collected during an interview included: socio-demographic and clinical features, habits before sleeping, environmental factors that could affect sleeping, the geriatric depression scale and Athens insomnia scale. Logistic regression analysis was done to find out the independent predictors of insomnia.Results: The prevalence of insomnia was 62.1%. The logistic regression revealed that insomnia is less likely among elderly of 75 and more (AOR=0.3) compared to those aged 60-75 years. The risk of insomnia is high among those with depression (AOR=6.4 and 14.6 for mild and moderate/severe depression; respectively), fear of death (AOR=14.7), life stressors (AOR=7.1), presence of musculoskeletal disorders (AOR=5.6), respiratory disorders (AOR=4.5), worry about children (AOR=4.5) and cold bedroom (AOR=2.7).Conclusion: Slightly less than two-thirds of the studied subjects have insomnia, and most of the associated factors are preventable and/or controllable.Recommendations: According to the results of the present study, the following recommendations are suggested: Design educational program for elders to enhance sleep through emphasizing on the importance of sleep hygiene practice, behavioral and non-pharmacological interventions, and healthy lifestyle.